Attention deficit hyperactivity disorder and developmental coordination disorder: Two separate disorders or do they share a common etiology. - Goulardins, J.; Rigoli, D.; Licari, M.; Piek, Jan; Hasue, R.; Oosterlaan, J.; Oliveira, J. (Elsevier, 2015)
Attention deficit hyperactivity disorder (ADHD) has been described as the most prevalent behavioral disorder in children. Developmental coordination disorder (DCD) is one of the most prevalent childhood movement disorders. The overlap between the two conditions is estimated to be around 50%, with both substantially interfering with functioning and development, and leading to poorer psychosocial outcomes. This review provides an overview of the relationship between ADHD and DCD, discussing the common presenting features, etiology, neural basis, as well as associated deficits in motor functioning, attention and executive functioning. It is currently unclear which specific motor and cognitive difficulties are intrinsic to each disorder as many studies of ADHD have not been screened for DCD and vice-versa. The evidence supporting common brain underpinnings is still very limited, but studies using well defined samples have pointed to non-shared underpinnings for ADHD and DCD. The current paper suggests that ADHD and DCD are separate disorders that may require different treatment approaches.